Melatonin and Sleep Disturbances in Children With Atopic Dermatitis - Dwiyana RF; Nuraeni L; Diana IA; Effendi RMRA; Gondokaryono SP; Ruchiatan K; Hindritiani R; Gunawan H (Dove Medical Press, 2022)
Reiva Farah Dwiyana, Lita Nuraeni, Inne Arline Diana, Raden Mohamad Rendy Ariezal Effendi, Srie Prihianti Gondokaryono, Kartika Ruchiatan, Reti Hindritiani, Hendra Gunawan Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran-Dr. Hasan Sadikin Hospital, Bandung, West Java, IndonesiaCorrespondence: Reiva Farah Dwiyana; Lita Nuraeni, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, 40161, Indonesia, Email reiva@unpad.ac.id; litanuraeni757@gmail.comObjective: To evaluate the correlation between melatonin levels and sleep quality, based on the Children's Sleep Habit Questionnaire (CSHQ), among children with atopic dermatitis (AD).Methods: This was an analytic study with a cross-sectional design involving two groups, AD children as the case group and participants without AD as the control group, conducted at the Pediatric Dermatology Clinic of Dr. Hasan Sadikin Hospital, Bandung, Indonesia. Melatonin levels and CSHQ score in the case group were compared to that in the control group. Correlation analysis was performed between melatonin levels and sleep quality based on CSHQ in the case group.Results: Participants in this study consisted of 19 children with moderate AD, (no patient with mild and severe AD was recruited), and 19 participants without AD. The mean CSHQ score in the case group was significantly higher than the control group (47.84 vs 36.79; p< 0.05). The mean melatonin level in the case group was significantly lower than the control group (320.18 pg/mL vs 383.86 pg/mL; p< 0.05). Comparative analysis was conducted using independent t-test. There was a significant Pearson's correlation index between SCORAD and CSHQ (p< 0.05). However, there was no correlation between melatonin levels and CSHQ, as well as between melatonin levels and SCORAD (p< 0.05).Conclusion: Children with moderate AD have impaired sleep quality and lower melatonin levels compared to controls. No correlation was found between melatonin levels and CSHQ, as well as melatonin levels and SCORAD, although there was a strong and significant correlation between SCORAD and CSHQ. Therefore, melatonin levels may not be the main cause of sleep disturbances in children with moderate AD.Keywords: atopic dermatitis, CSHQ, melatonin, SCORAD